Reducing Nitrogen Input in Barley Crops While Maintaining Yields Using an Engineered Biostimulant Derived From Ascophyllum nodosum to Enhance Nitrogen Use Efficiency - Goñi, Oscar; Łangowski, Łukasz; Feeney, Ewan; Quille, Patrick; O’Connell, Shane (Frontiers in Plant Science, 2021)
IIntensive agricultural production utilises large amounts of nitrogen (N) mineral fertilisers that are applied to the soil to secure high crop yields. Unfortunately, up to 65% of this N fertiliser is not taken up by crops and is washed from the field. To compensate these issues, growers usually apply more fertiliser than crops actually need, contributing significantly to N pollution and to GHG emissions. In order to combat the need for such large N inputs, a better understanding of nitrogen use efficiency (NUE) and agronomic solutions that increase NUE within crops is required. The application of biostimulants derived from extracts of the brown seaweed Ascophyllum nodosum has long been accepted by growers as a sustainable crop production input. However, little is known on how Ascophyllum nodosum extracts (ANEs) can influence mechanisms of N uptake and assimilation in crops to allow reduced N application. In this work, a significant increase in nitrate accumulation in Arabidopsis thaliana 6 days after applying the novel proprietary biostimulant PSI-362 was observed. Follow-up studies in barley crops revealed that PSI-362 increases NUE by 29.85-60.26% under 75% N input in multi year field trials. When PSI-362 was incorporated as a coating to the granular N fertiliser calcium ammonium nitrate and applied to barley crop, a coordinated stimulation of N uptake and assimilation markers was observed. A key indicator of biostimulant performance was increased nitrate content in barley shoot tissue 22 days after N fertiliser application (+17.9-72.2%), that was associated with gene upregulation of root nitrate transporters (NRT1.1, NRT2.1, and NRT1.5). Simultaneously, PSI-362 coated fertiliser enhanced nitrate reductase and glutamine synthase activities, while higher content of free amino acids, soluble protein and photosynthetic pigments was measured. These biological changes at stem elongation stage were later translated into enhanced NUE traits in harvested grain. Overall, our results support the agronomic use of this specialised ANE that allowed a reduction in N fertiliser usage while maintaining or increasing crop yield. The data suggests that it can be part of the solution for the successful implementation of mitigation policies for water quality and GHG emissions from N fertiliser usage.